(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims at analyzing the indicators of the sovereign credit of oil and without oil to determine the face of the Iraqi economy from the challenges that would impede the process of growth and economic development for the period (2004-2015). the research tries to show some lessons to be learned from those indicators, Many of the most important conclusions, acceptance of the hypothesis of research and the weakness of sovereign credit capacity in Iraq to bear the sovereign debt and its burden and work to achieve sustainable economic and social development "in an economy in which oil is neutralized as a single commodity depends on them to meet the requirements of efficiency and efficiency The index of the ratio of imports to exports without oil reflects in real terms the ability of the economy to bear the burden of imports, and that the high rates of this index by more than 100%, it demonstrates the weakness of the Iraqi economy and to the significant decline in the credit rating of Iraq and thus weakening its creditworthiness without oil . And recommended the research to invest in the productive sectors and encourage exports through the formation of an export sector and follow the strategy of production for export, as well as investment in government securities, along with oil revenues, and tax revenues and revitalize the tourism sector, To be an effective supporter in supporting the budget without resorting to borrowing to fill the deficit.